The mystery of the Shemitah: the 3000-year-old mystery that holds the secret of America's future, the world's future... and your future! - Cahn, Jonathan (Lake Mary, FL : FrontLine, 2014)
Cahn shows that financial and economic events of today are influenced by the two ancient Biblical cycles: the 7 year Sabbath cycle and the 50 year Jubilee cycle. He shows how the cycles have foretold the greatest crashes in Wall Street history, the timing of 9/11, the world wars and the collapse of nations, world powers, and empires... and your life....
Includes bibliographical references (pages 274-275).
Keywords: Prophecy -- Christianity; Sabbatical year (Judaism)